2021
DOI: 10.18043/ncm.82.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Barriers and Facilitators to Prenatal Care for Spanish-Speaking Women

Abstract: background Early access to quality prenatal care is an essential component of improving maternal and neonatal outcomes as it allows for early intervention and risk stratification. Women who receive late or infrequent prenatal care are at high risk for complications including preterm birth, infant death, and stillbirth. We sought to better understand the barriers Spanish-speaking women face in accessing quality prenatal care and to identify facilitators in obtaining timely quality prenatal care. methods We recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…These shifts in policy may not apply to all clinical sites as the clinical care environment in Florida is unique, and each state and locale has a unique patchwork of prenatal care practitioners and barriers to access. Nonetheless, many states in the United States face similar challenges in assuring access to early prenatal care for all 8,15,16,30,42 . In addition, many modifiable factors at the health care system level were identified, including expanding Medicaid coverage for all people who are, or who have the capacity to become, pregnant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These shifts in policy may not apply to all clinical sites as the clinical care environment in Florida is unique, and each state and locale has a unique patchwork of prenatal care practitioners and barriers to access. Nonetheless, many states in the United States face similar challenges in assuring access to early prenatal care for all 8,15,16,30,42 . In addition, many modifiable factors at the health care system level were identified, including expanding Medicaid coverage for all people who are, or who have the capacity to become, pregnant.…”
Section: Discussionmentioning
confidence: 99%
“…Open‐ended surveys were administered in English or Spanish, and they included the following: (a) demographic questions about age, race, ethnicity, nativity, acculturation (as defined in the Short Acculturation Scale for Hispanics questionnaire), marital status, income, education level, parity, insurance type (before, during, and after pregnancy), and substance abuse engagement during pregnancy 29 ; (b) pregnancy characteristics and parental clinic conditions (eg, distance to the clinic, method of transportation); and (c) an in‐depth examination of specific barriers to prenatal care access. Questions about barriers were developed from pilot testing 30 . Each participant received a $25 gift card as compensation for participation.…”
Section: Methodsmentioning
confidence: 99%
“…37 Experiences of discrimination and access to care barriers have also been documented among Latinx birthing people. 38 40 In 2020, Fryer et al found that Spanish-speaking women reported barriers related to discrimination based on undocumented status and language barriers stemming from a lack of interpretation services. 40 While the results of this study did not indicate that Latinx participants had experiences with programs that improved their access to community and social resources (e.g.…”
Section: Discussionmentioning
confidence: 99%
“… 38 40 In 2020, Fryer et al found that Spanish-speaking women reported barriers related to discrimination based on undocumented status and language barriers stemming from a lack of interpretation services. 40 While the results of this study did not indicate that Latinx participants had experiences with programs that improved their access to community and social resources (e.g. Fresno Barrios Unidos), this could be a byproduct of the data collection approach which oversampled Black/African American pregnant people by engaging Black Infant Health clients.…”
Section: Discussionmentioning
confidence: 99%
“…From 2018 to 2019, the percentage of mothers who began prenatal care in the rst trimester also decreased among Hispanic women, while it increased for other races/ethnicities (2). Hispanic women face signi cant language barriers, not nding culturally competent healthcare providers, and ethnic discrimination are main barriers that Hispanic women face to access early prenatal care (14).…”
Section: Introductionmentioning
confidence: 99%